Penerapan model pembelajaran situation based learning (sbl) untuk meningkatkan keterampilan pemecahan masalah materi skala pada peserta didik kelas V sekolah dasar - Dinda Maharani Ayuning Marga; Siti Kamsiyati; Anesa Surya (Didaktika Dwija Indria, 2022)
Abstract. The purpose of the research is to improve the problem solving skills of scale by applying by Situation Based Learning models.. This research is a Classroom Action Research with two cycles. Students of the 5th studens of SDN Setono 95 Surakarta in the 2019/2020 academic, totally 25 students are the subjects. Data collection techniques are using observation, interviews, documentation, and tests. Data validity test are using triangulation technique. Interactive model Miles-Huberman was used to data analysis techniques. The initial conditions of abillity show 4% achievement or as much as 2 student. In the first cycle, the first meeting experienced an increase of 16% and the second meeting was 32%. Learning is continued with the second cycle of the first meeting with a percentage of 68% and the second meeting of 84%.. Based on the results, it can be concluded that application of the Situation Based Learning models can improve problem solving skills in class V SDN Setono 95 Surakarta for the 2019/2020 academic year.